Post-test simulation of the HTR-10 reactivity insertion without scram. (June 2016) - Chen, Fubing; Dong, Yujie; Zhang, Zuoyi
Highlights: At present, the HTGR demonstration NPP, i.e., the HTR-PM is under construction. It is of importance to check the design software against actual test results. This study is about the validation of the THERMIX code using the test data from the HTR-10 which is the only pebble bed HTGR under operation. Through the validation results, the code is proved to be an effective tool to simulate similar accident scenarios for the HTR-PM. Abstract: The 10 MW high temperature gas-cooled reactor-test module (HTR-10) is the first high temperature gas-cooled reactor (HTGR) in China. After the commissioning phase, several safety demonstration tests, focusing on simulating the anticipated transient without scram (ATWS) scenarios, were successfully performed on this reactor. Among these tests, a reactivity insertion ATWS test was conducted in November, 2003 by withdrawing a single control rod with no activation of the reactor shutdown system. This test was carried out at 30% rated power, i.e., 3 MW power level, with about 1‰ Δ k / k positive reactivity introduced into the core. In this study, the HTR-10 dynamic response during the reactivity insertion ATWS test is simulated and analyzed with the help of the THERMIX code. The inherent safety features of the HTR-10 are revealed and verified by both the test and the simulation results. Important physical phenomena, e.g., automatic shutdown, reactor recriticality, power oscillation, helium natural circulation and temperature redistribution, are investigated. Based on the actual test conditions, the simulation reproduces the reactor transients very well. For the reactor power and the temperatures of its internals, the code results are compared with their corresponding measured values. Good agreement between the calculation results and the test results proves the THERMIX simulation capability for the HTR-10 transient behavior during the reactivity insertion ATWS test. As the most important safety-related parameter, the maximum fuel temperature during the test process is always much lower than its safety limit of 1620 °C.